If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4y + 3z = 12 Solving 6x + 4y + 3z = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 6x + 4y + -4y + 3z = 12 + -4y Combine like terms: 4y + -4y = 0 6x + 0 + 3z = 12 + -4y 6x + 3z = 12 + -4y Add '-3z' to each side of the equation. 6x + 3z + -3z = 12 + -4y + -3z Combine like terms: 3z + -3z = 0 6x + 0 = 12 + -4y + -3z 6x = 12 + -4y + -3z Divide each side by '6'. x = 2 + -0.6666666667y + -0.5z Simplifying x = 2 + -0.6666666667y + -0.5z
| (2x^1/4)^3 | | 20-4y=8 | | 5x^2-35=55 | | X+8+2x=15 | | 258951481+154848911292362962592929191416129864189149519818918418391371326222643262346242545246249632426462462464242+219429429249246432364234624624642964234624= | | x^3-17x^2+72x=p | | 1-1/2x=1/2-1/2x | | 5x-25=4x-55 | | Y=10x^2-10x | | 30-7n=n-2(1+8n) | | 642542364242+245624+6246246246426424624+242652= | | x^2-17x+72x=0 | | 43+3=15 | | -n-4=-13 | | 7x+40=2x | | 14x-25=9x | | 11x^2+10x-8=0 | | (14a+6)*5-54= | | -4w+20=60 | | 6X=-37+7 | | 4x-9y-11y+2x+10=0 | | d/13__-3 | | -10+5x=-100 | | -7n-7=-35 | | x^2-95x+7=0 | | 1/6x-1/2=-42 | | 5x-2+7=25 | | 4d+6=10+2d | | f(x)=x^3-5x^2-16x+80 | | 4x+6x=20-10 | | .003x-.002=.07 | | 70x^2-73x+9=0 |